2022
DOI: 10.1039/d1tb01892b
|View full text |Cite
|
Sign up to set email alerts
|

FeMoO4nanospheres-based nanozymatic colorimetry for rapid and sensitive pyrophosphate detection

Abstract: Assays of pyrophosphate ion (PPi) are of remarkable biochemical significance due to its vital roles in the bioenergetic and metabolic processes or as the disease indicators. Colorimetry is popular in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…To identify the type of ROS, terephthalic acid (TA) was used as an indicator because TA can be oxidized to 2-hydroxy terephthalic acid (TAOH) with blue fluorescence in the presence of ˙OH. 38 As shown in Fig. S8 (ESI†), the fluorescence spectra demonstrated that an obvious fluorescence emission peak at about 430 nm emerged in a mixture consisting of glucose, Al/Fe-TCPP NMOF/GO x and TA.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…To identify the type of ROS, terephthalic acid (TA) was used as an indicator because TA can be oxidized to 2-hydroxy terephthalic acid (TAOH) with blue fluorescence in the presence of ˙OH. 38 As shown in Fig. S8 (ESI†), the fluorescence spectra demonstrated that an obvious fluorescence emission peak at about 430 nm emerged in a mixture consisting of glucose, Al/Fe-TCPP NMOF/GO x and TA.…”
Section: Resultsmentioning
confidence: 86%
“…S8 (ESI †), the fluorescence spectra demonstrated that an obvious fluorescence emission peak at about 430 nm emerged in a mixture consisting of glucose, Al/Fe-TCPP NMOF/GOx and TA. 38 In contrast, no fluorescence emission was observed in the mixture of TA with glucose or Al/Fe-TCPP NMOF/ GOx. The results confirmed that the ROS generated in the mixture of glucose, TA and Al/Fe-TCPP NMOF/GOx were OH.…”
Section: Gsh Consumption and Cascade Catalytic Properties Of Al/fe-tc...mentioning
confidence: 98%
“…The correlation coefficient (R 2 ) is fairly good (R 2 = 0.993), favorable to attain an impressive LOD of 0.68 nM for PPi. The analytical efficiency of the coffee-Tryp-CuNCs-based fluorescence sensor is compared to the reported approaches [38][39][40][41][42][43][44][45][46][47][48][49][50][51] for detecting of OH and PPi, as shown in Tables 1 and 2.…”
Section: Sensitivity Of Coffee-tryp-cuncs Towards Oh and Ppimentioning
confidence: 99%
“…Electrochemical methods provide a compelling alternative for AFZ detection, due to their simplicity, speed, cost-effectiveness, and sensitivity [13][14][15][16][17][18][19]. Electrochemical sensors operate based on the redox reactions of the analyte at the electrode surface, generating a measurable current or potential signal [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%